Case studies in neurological pain - Sommer, C. (Claudia) (Cambridge University Press, 2012)
"Among all patients with neurological disorders, pain is probably the most common symptom experienced. Identifying, understanding and treating pain is a responsibility of health care providers in all branches of neurology. This text is about pain in neurological diseases, both 'neuropathic' pain that is recognized in sensory neuron disorders but also other types of pain less commonly considered. These latter disorders include for example, pain in Parkinson's disease, ALS and muscle diseases. The text includes specific chapters on mechanisms of neuropathic pain, updated with new ideas on its pathogenesis, and a summary of recent therapeutic guidelines. Most of the text however centers on actual patient encounters at the Neurology clinics of the Universities of Wurzburg and Calgary. This emphasis is to make the vignettes relevant to clinical practitioners but also to introduce researchers and workers in industry to the complex and challenging issues faced during direct patient encounters. Therapeutic failures are common among our vignettes, highlighting the fact that current therapeutic advances remain inadequate-a challenge for researchers to find better approaches"--Provided by publisher.